Scalability, venture capital availability, and unicorns: Evidence from the valuation and timing of IPOs - Somaya, Deepak; You, Jingya (Journal of Business Venturing, 2024)
The growing phenomenon of highly valued startups (e.g., unicorns) poses fundamental questions for entrepreneurship research. We posit that venture scalability and VC funding availability may explain startups' IPO valuations (and timing). Highly scalable ventures may not only capture very large market opportunities, but their scaling strategies may also be constrained by the governance and regulatory burdens faced by public firms. Accordingly, we hypothesize and find that more scalable ventures undertake IPOs at higher valuations, which is positively moderated by VC funding availability. Highly scalable startups also delay their IPOs for longer but only when VC funding availability is high.